2011
DOI: 10.4141/cjps2011-047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ammonium sulfate and water hardness on glyphosate and glufosinate activity in corn

Abstract: Soltani, N., Nurse, R. E., Robinson, R. E. and Sikkema, P. H. 2011. Effect of ammonium sulfate and water hardness on glyphosate and glufosinate activity in corn. Can. J. Plant Sci. 91: 1053–1059. Eight field trials were conducted over a 3-yr period (2008 to 2010) near Harrow and Ridgetown, Ontario, to evaluate the effect of water hardness (distilled: 0 ppm; intermediate: 353 ppm; and very hard 1799 ppm) on full label doses of glyphosate (900 g a.e. ha−1) and glufosinate (400 g a.i. ha−1) [with and without ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…The authors evaluated Urochloa platyphylla, Ipomoea lacunosa, Amaranthus palmeri, and Cyperus esculentus. On the other hand, Soltani et al (2011) observe no differences in the control of various monocot and dicot weeds using water with different degrees of hardness (0, 353, and 1,799 ppm). This divergence of results could also be observed in the study of Manuchehri et al (2018).…”
Section: Areamentioning
confidence: 74%
See 1 more Smart Citation
“…The authors evaluated Urochloa platyphylla, Ipomoea lacunosa, Amaranthus palmeri, and Cyperus esculentus. On the other hand, Soltani et al (2011) observe no differences in the control of various monocot and dicot weeds using water with different degrees of hardness (0, 353, and 1,799 ppm). This divergence of results could also be observed in the study of Manuchehri et al (2018).…”
Section: Areamentioning
confidence: 74%
“…Interference in the effectiveness of the applied product is rarely observed if only the pH is changed. Soltani et al (2011) found no differences in weed control (Abutilon theophrasti, Amaranthus retroflexus, Chenopodium album, and other grasses) with glyphosate using water with varying degrees of hardness.…”
Section: Introductionmentioning
confidence: 79%
“…Pratt et al (2003) showed that hard water, defined as 500 mg L -1 CaCO 3 , reduced velvetleaf (Abutilon theophrasti L.) control by glyphosate while addition of AMS increased control. Although most of the research literature indicates that AMS can improve glyphosate efficacy (Wills and McWhorter 1985;Salisbury et al, 1991;Young et al, 2003), some authors reported no benefit of added AMS on glyphosate (Nurse et al, 2008;Soltani et al, 2011). Differential responses between weed species were noted by the authors.…”
Section: Introductionmentioning
confidence: 88%
“…ha -l , ammonium sulphate at 2% (w/v) in a distilled water spray carrier enhanced toxicity to H. annuus from 11 to 55% fresh weight reduction but reduced glyphosate toxicity in K. scoparia and G. max. Soltani et al (2011) reported no effect of water hardness on A. theophrasti, A. retroflexus, Chenopodium album, Setaria viridis and Echinochloa crus-galli control, when glyphosate was applied with or without AMS. With the widespread occurrence of glyphosate 3 resistant (GR) weeds, and because the effect of hard water and AMS on glyphosate toxicity is species dependent, optimum weed control in different species should be studied in weed species in more detail.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation